Pengaruh Likuiditas, Struktur Modal, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Garmen dan Tekstil yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Sofia Masytha Salsabila; Maula Alfina Maulidah; Istiono Istiono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the effect of liquidity, capital structure, and profitability on firm value in garment and textile companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Firm value is an important indicator that reflects the company's performance and prospects in the capital market, so it is influenced by various internal factors, including liquidity, capital structure, and profitability. This study uses a quantitative approach with multiple linear regression analysis methods. The research sample was selected by purposive sampling based on the criteria of companies that had complete financial data during the study period. Secondary data were obtained from annual financial reports published on the IDX. Prior to regression analysis, a classical assumption test was performed to ensure the validity of the model. The study shows that capital structure and profitability have a significant effect on firm value, while liquidity has no significant direct effect. These findings indicate the importance of managing capital structure and increasing profitability to increase firm value in the garment and textile sector. This research is expected to be a reference for company management and investors in making strategic decisions amid the challenges of an increasingly competitive industry.